Insight into functional microorganisms in wet–dry conversion to alleviate the toxicity of chromium fractions in red soil - Liu, Hongwei; Yuan, Ruiling; Sarkodie, Emmanuel Konadu; Tang, Jiahui; Jiang, Luhua; Miao, Bo; Liu, Xueduan; Zhang, Siyuan (Frontiers in Microbiology, 2022)
Soil contamination with potentially toxic element such as chromium (Cr) poses a threat to the environment and human health. The environmental toxicity of Cr is related not only to the total Cr content but also to the distribution of Cr fractions. In this study, laboratory simulation experiments were conducted to explore the characteristics of Cr fractions and responses of the functional microbial community during dynamic leaching and static drying processes. The results showed that acid-soluble Cr and reducible Cr transformed into other relatively stable fractions under dry conditions, and ammonium nitrogen promoted the transformation. Nitrate-nitrogen was significant positively correlated with Cr fractions in the wet stage (P < 0.05), while ammonium nitrogen showed the same relation in the dry process. Analysis of the microbial community showed that the bacterial and fungal genera Flavihumibacter, Altererythrobacter, Methylobacillus, Flavisolibacter, Lysobacter, and Cladosporium were related to the Cr fractions (acid-soluble Cr, reducible Cr and oxidizable Cr) under wet conditions, while the microbial genera Ellin6067, MND1, and Ramlibacter were related to Cr fractions under dry conditions. Moreover, the proliferation of the functional microbial genera Methylobacillus, Ellin6067, and MND1 related to Cr fractions in the wet–dry conversion process alleviated the environmental toxicity of Cr. These findings provide useful information for the remediation of Cr-contaminated soils by monitoring the distribution fractions of Cr and the functional microbial community under wet–dry conditions.